(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The study and analysis of the global oil market in isolation from the role of the policies of international oil organizations, especially the International Energy Agency (IEA), is tainted by a lack of analysis of the influencing factors and consequently the final results for them, as the impact of these policies is often greater and with different durations of time than other market factors. Therefore, it is important to analyze the policies of the oil organizations and the extent of their impact on the oil markets in the short, medium and long term, for a more accurate and broader analysis of the global energy balance, and the supply and demand for oil at the present and future, in order to predict the path of global oil markets to find out the factors supporting market stability, especially oil prices that It is a reference to other energy prices and their future plans, and in light of the fundamental developments that the markets have witnessed during the past three decades, as the trends of supply and demand for oil were characterized by the inability to continue in the future in the current form from the economic, social and environmental perspective, this on the one hand, and on the other hand economic growth depends To the world on the extent of its success in securing energy sources that meet future needs, in light of the challenges of the safety of energy supplies, especially oil ones, and the development of energy alternatives and their gradual replacement, and here emerges the role of the International Energy Agency on the global oil market.